MENINGKATKAN HASIL BELAJAR MAHASISWA DENGAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR DAN KEAKTIFAN BELAJAR - Gulyanto, Bambang (Smart Education, 2025)
Abstract: The Project Based Learning model is an alternative in improving learning outcomes and learning activities. Learning outcomes are changes in behavior that students obtain after participating in the teaching and learning process. Learning outcomes can be in the from of knowledge, attitudes, skills, habits, and abilities. Meanwhite, learning activeness in the involvement of students in the learning process both physically and mentally. Learning outcomes in the 3rd semester Currculum & Learning course, Indonesia Language and Literature Study Program FKIP Asahan University for the 2024/ 2025 cademic year can increase using Project Based Learning model, namely in the pre-ccle 33,33%, cycle I to 66,67% and in cycle II to 100%. The Project Based Learning model changes tradional teacher- oriented learning into student-oriented learning. Keywords: Project Based Learning, Learning Outcomes, Learning Activities. Abstrak: Model Project Based Learning merupakan sebuah alternatife dalam meningkatkan hasil belajar dan aktifitas belajar. Hasil belajar adalah perubahan prilaku yang diperoleh peserta didik setelah mengikuti proses belajar mengajar. Hasil belajar dapat berupa pengetahuan, sikap, keterampilan, kebiasaan, dan kemampuan. Sedangkan keaktifan belajar merupakan keterlibatan peserta didik dalam proses pembelajaran baik secara fisik maupun mental. Hasil belajar pada mata kuliah Kurikulum & Pembelajaran semester 3 Program Studi Bahasa dan Sastra Indonesia FKIP Universitas Asahan tahun ajaran 2024/2025 dapat meningkat dengan menggunakan model Project Based Learning yaitu pada prasiklus 33,33%, siklus I menjadi 66,67% dan pada siklus II menjadi 100%. Model Project Based Learning merubah pembelajaran tradional yang berorientasi pada guru, menjadi pembelajaran yang berorientasi pada peserta didik. Kata kunci: Project Based Learning, Hasil Belajar, Aktifitas Belajar